An Examination of Recidivism Among Inmates Released From a Private Reentry Center and Public Institutions in Colorado - Powers, Ráchael A. (The prison journal, 2017)
In this study, we examine comparative rates of recidivism for Colorado inmates released from a private reentry center and public facilities. Using a sample of 6,102 inmates released from 2008 to 2012, we measure overall recidivism and recidivism for a new crime. Applying a quasi-experimental methodology, we find that overall rates of recidivism are comparable. Prior to matching, 46.8% of the treatment and 61.3% of the comparison group recidivated, and the difference is statistically significant. However, after matching on relevant covariates, the difference was reduced to nonsignificance. In contrast, those released from the private facility are more likely to return to prison for a new offense. Approximately 14% of those in the private facility committed a new crime compared with 9% prematching and 8% postmatching. Despite these modest differences in the rate of recidivism, the overall time to return to prison is comparable between the groups.